2021
DOI: 10.1126/sciadv.abg1964
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic adaptation evoked by arginine enhances the effect of radiation in brain metastases

Abstract: Arginine enhances the effect of radiation in patients with brain metastasis by metabolic suppression of cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Recently, another opposing strategy for radiosensitization in solid tumors was reported. Rossella Marullo et al demonstrated that administration of oral L-arginine induced radiosensitization and local control in patients who underwent standard radiation therapy 112 , which is associated with increased DNA damage via nitric oxide (NO)-mediated metabolic suppression 112 . It is worth mentioning that NO plays a dual role in tumor cells.…”
Section: Amino Acid Metabolism and Cancer Radioresistancementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another opposing strategy for radiosensitization in solid tumors was reported. Rossella Marullo et al demonstrated that administration of oral L-arginine induced radiosensitization and local control in patients who underwent standard radiation therapy 112 , which is associated with increased DNA damage via nitric oxide (NO)-mediated metabolic suppression 112 . It is worth mentioning that NO plays a dual role in tumor cells.…”
Section: Amino Acid Metabolism and Cancer Radioresistancementioning
confidence: 99%
“…An appropriate amount of NO can promote tumor growth; however, either too low or too high a level of NO will limit the proliferation of tumor cells. Since arginine is a precursor to NO 112 , 113 , it may explain the contradiction between ADT and oral L-arginine.…”
Section: Amino Acid Metabolism and Cancer Radioresistancementioning
confidence: 99%
“…With accompanying ICD, more mature DC infiltrations (Figure m) and increased secretions of various lymphatic chemokines (Figure s) indicate that the recruitment of effector T cells in tumors will be gradually escalated. In addition, the residual l -Arg is also inferred to contribute to the enhanced immunotherapy due its immune potentiation effects. These compelling results and multiple immune-stimulant actions adequately validate that such intratumorally synthesized in situ Au bioreactor-enhanced microwavegenetics can propel immune activation, immune cell infiltration, ITM mitigation, and reverse immune-desert TME, which can highlight CAT-T cell infiltrations into solid tumors.…”
Section: Resultsmentioning
confidence: 82%
“…[38] In this study, we observed a significant metabolic behavior change in melanoma cells after APAP-P-NO treatment, which was probably due to the inactivation of metabolism-related key enzymes upon S-nitrosylation modification. [39] Of note, most immunosuppressive metabolites in the TME, such as lactate, are secreted by tumor cells themselves, and thus ONOO − mediated intracellular metabolic homeostasis disruption may cut off the metabolic crosstalk between tumor cells and the TME, favoring antitumor immune responses. [40] Indeed, this highly specific ONOO − intervention effectively reversed the immunosuppressive TME via TAMs polarization from M2-type to M1-type, reduction of MDSCs and Tregs, and CD8 + T cells restoration, eventually turning immunologically "cold" tumors "hot".…”
Section: Discussionmentioning
confidence: 99%